2017
DOI: 10.3390/toxins9070203
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Association among Mycotoxins and other Variables in Children with Autism

Abstract: Environmental factors and genetic susceptibility are implicated in the increased risk of autism spectrum disorder (ASD). Mycotoxins are agricultural contaminants of fungal origin that represent real risk factors for human health and especially for children. Thus, the main hypothesis of this work is that the deterioration of the clinical manifestation of autism in children may result from the exposure to mycotoxins through the consumption of contaminated food. Within a cross-sectional study, a group of autistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 53 publications
2
37
0
Order By: Relevance
“…Human urinary analysis focused on free FB with FB1 as the most prevalent next to FB2 and FB3 (Cirlini et al., ; De Santis, et al., ; Gerding et al., ; Gong, Shirima, Srey, Kimanya, & Routledge, ; Solfrizzo, Gambacorta, & Visconti, ; Torres et al., ). However the mean FB1 levels found in urine have been low, for instance 0.07 ng/mL (Cirlini et al., ), 0.4 ng/mL (De Santis, et al., ), 0.44 ng/mL (Gerding et al., ), 1.38 ng/mL (Gong, et al., ), and 0.05 ng/mL (Solfrizzo et al., ). Moreover, a statistically significant correlation between the estimated FB intake and the urinary FB1 levels based on the Pearson product correlation was observed ( r = 0.26, p = 2.13 × 10 −17 , n = 1229) (Torres et al., ).…”
Section: Fumonisins (Fb)mentioning
confidence: 99%
“…Human urinary analysis focused on free FB with FB1 as the most prevalent next to FB2 and FB3 (Cirlini et al., ; De Santis, et al., ; Gerding et al., ; Gong, Shirima, Srey, Kimanya, & Routledge, ; Solfrizzo, Gambacorta, & Visconti, ; Torres et al., ). However the mean FB1 levels found in urine have been low, for instance 0.07 ng/mL (Cirlini et al., ), 0.4 ng/mL (De Santis, et al., ), 0.44 ng/mL (Gerding et al., ), 1.38 ng/mL (Gong, et al., ), and 0.05 ng/mL (Solfrizzo et al., ). Moreover, a statistically significant correlation between the estimated FB intake and the urinary FB1 levels based on the Pearson product correlation was observed ( r = 0.26, p = 2.13 × 10 −17 , n = 1229) (Torres et al., ).…”
Section: Fumonisins (Fb)mentioning
confidence: 99%
“…To address these limitations, Devreese et al [29] developed simple acetonitrile solvent precipitation method in combination with LC-MS for measurement of 13 mycotoxins in pig plasma suitable for toxicological studies, but the limits of quantitation (2-10 ng/mL) [29] do not make this method adaptable to human biomonitoring. Similarly, De Santis et al [30] combined pronase treatment, acidified ethyl acetate LLE and QuEChERS with LC-MS detection for the analysis of 8 mycotoxins, but the method showed insufficient limit of quantifications (LOQs) for accurate quantitation (mean values for positive samples below LOQ) and significant susceptibility to matrix effects for several of the analytes despite extensive clean-up. Tolosa et al [31] developed dispersive liquidliquid microextraction method using ethyl acetate in combination with LC-MS/MS for…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Devreese et al [28] used 0.1% AA and 0.01% AA for their multi-mycotoxin and zearalenone class-specific methods, respectively and state that these modifiers provided the best sensitivity [27], but the extent of improvement was not reported. Osteresch et al [30] proposed the use of AA gradient and showed it provided better separation and S/N ratios than FA, but different gradients were tested for the two modifiers precluding direct side-by-side comparison. However, the potential of AA to increase signal intensity in ESI(-) was previously shown for other types of compounds.…”
Section: Effect Of Mobile Phase Additives On Ionization Efficiencymentioning
confidence: 99%
“…Among the published methods for mycotoxin determination in biological samples, including HPLC [20,31,32], GC-MS/MS [33], LC-MS [34,35], LC-MS/MS [4,18,36,37], and LC-HRMS [38], LC-MS/MS provides remarkable selectivity, accuracy and sensitivity. Most of the methods were applied to detect common regulated mycotoxins [4,5,8,19,32,37,[39][40][41][42], employing various sample preparation strategies such as the "dilute and shoot" approach [4,5,37,41], QuEChERS [15], liquid-liquid extraction (LLE) [20], immunoaffinity (IAC) columns [41,42], solid phase extraction (SPE) [18], and various combinations of these techniques [13].…”
Section: Introductionmentioning
confidence: 99%